Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content: 1. The impact of using artificial intelligence methods on improving the quality of supply services in the government sector: An applied study on the Ministry of Human Resources and Social Development in the Kingdom of Saudi Arabia Ms. Wesa GhareebAlshehri, Dr. Sumia Ibrahim Ahmad Abdallah 2. The impact of implementing electronic education through the Madrasati platform and its relationship to the level of job satisfaction among teachers in the Mecca region Ms. Badriah Mohammad Alotaibi 3. The reality of the application of social responsibility among the companies of the Saudi telecom sector during (Covid-19) Ms. Fawziah Rashed Alotibi, Dr. Samia Ayed Aljaeed 4. The impact of job empowerment on the performance of female employees at Umm Al-Qura University in Mecca, 2021. Ms. Ashwaq Saeed Al-Ghamdi 5. Administrative organization and its impact on achieving institutional excellence: An Applied Study on Abdul Latif Jameel Company Mr. Badr Mohammed Al Harithi 6. The relationship between women leadership Styles and organizational health Mrs. Faten Zuhair Ahmed Al-Saati, Dr. Ghada Abdel Rahman Al-Anqari 7. The impact of tourism sector variables on economic growth in the Kingdom of Saudi Arabia during the period 2010-2020 Dr. Ebtihag Hashim Mohammed Elgzoli